Corporate finance practices in Sri Lanka - Kengatharan, L. (AESS Publications, 2018)
The aim of this study was to investigate the use of corporate finance practices in terms of capital budgeting, cost of equity capital and capital structure in Sri Lanka. A comprehensive primary survey was conducted of 38 out of 150 financial officers of companies listed on the Colombo Stock Exchange (CSE) in Sri Lanka. Stratified random sampling was used to select the participants in order to represent the different sectors in CSE. Collected data were then analyzed by applying mean and percentage analysis. Results of the survey revealed that NPV was the most frequently ‘always’ cited capital budgeting method, followed by IRR and PB. CAPM was the most preferred method to calculate the cost of equity capital followed by average historical rate of return on common stock. Remarkably, most firms would use a discount rate for entire company to evaluate the project. Further, it was evaluated that how finance professionals make adjustments for risk factors. It was concluded that risk of unexpected inflation, interest rate risk, term structure risk, business cycle risk, size based risk, market to book ratio and momentum were mostly adjusted by discount rate while commodity price risk, foreign exchange risk and distress risk were mostly adjusted by cash flow. Further, this study was to find out whether Sri Lankan finance professionals behave as expected by pecking order theory of capital structure patterns. Findings of the study are in line with the pecking order theory that firms are having preference to internal finance for their capital. This research has proffered a more reliable and comprehensive analysis of corporate finance practices in Sri Lankan companies.
Keywords: Capital budgeting; Cost of equity capital; Capital structure; Discount rate; Cash flow; Corporate finance